Improving the productivity and efficiency of vascular surgery and radiology multidisciplinary meetings. Issue 1 (4th September 2015) - Dobson, Gary; Neeson, Declan
Abstract: Multidisciplinary team meetings are recognized as an important factor in driving quality of care. The Vascular Society of Great Britain and Northern Ireland recommend that all aspects of vascular surgery are suitable for discussion at multidisciplinary team (MDT) meetings, including carotid, peripheral, and aortic disease. The juniors doctors were tasked with preparing the patient list in our unit. This had become time consuming and somewhat unrewarding. The methods of preparation and information required on the patient list were reviewed. It was felt that typing a clinical summary for each patient on the list was the most time consuming factor. This was removed and patients were instead simply categorized into subgroups such as aneurysms, critical limb ischemia, and others. The information removed was substituted with the use on an electronic care record during the meeting to answer questions regarding comorbidities and previous interventions. Time spent preparing the meeting by the junior doctors was recorded before and after cycles of intervention. Prior to intervention this was found be a mean of 140 minutes (2.3 hours), and improved to a mean of 45 minutes (0.45 hours) with consequent cycles. The overall proportion of patients receiving definitive outcomes in each meeting after changes were implemented increased from 35 to 55%. This was not a primary outcome, but an unintended consequence of careful consideration of each cycle. In conclusion, the changes implemented have allowed junior doctors to spend more of their time with other activities such as the outpatient department (OPD) and theatre during their vascular surgery rotation. The proportion of cases discussed has increased due to more focused discussions during the MDT meeting, resulting in improved patient care. All stakeholders gave a largely positive reaction to the changes implemented.